Heated tobacco products and circulating high-density lipoprotein cholesterol concentrations - Huan Hu; Tohru Nakagawa; Toru Honda; Shuichiro Yamamoto; Toshiaki Miyamoto; Hiroko Okazaki; Masafumi Eguchi; Taiki Shirasaka; Takeshi Kochi; Isamu Kabe; Aki Tomizawa; Takako Miki; et al. (Scientific Reports, 2022)
Abstract We aimed to assess the association between heated tobacco product (HTP) use and high-density lipoprotein cholesterol (HDL-C) concentration. Our study included 12,268 workers from five companies (Study I) and 36,503 workers from another large company (Study II). Participants were categorized into five groups: never smokers, past smokers, exclusive HTP users, dual users of cigarettes and HTPs, and exclusive cigarette smokers. We analyzed the data of Studies I and II separately and then pooled these estimates using a fixed-effect model. Of the 48,771 participants, 9.3% were exclusive HTP users, and 6.0% were dual users. Exclusive HTP users had modestly but significantly lower concentrations of HDL-C than never smokers, with the pooled mean difference being − 1.1 (95% CI − 1.5 to − 0.6) mg/dL. Dual users showed a further reduction (mean difference − 3.7 (− 4.2 to − 3.2) mg/dL), which was comparable to that of exclusive cigarette smokers versus never smokers (mean difference − 4.3 (− 4.7 to − 3.9) mg/dL). The pooled odds ratios (95% CIs) of having low HDL-C (< 40 mg/dL for men and 50 mg/dL for women) were 1, 0.99 (0.90–1.11), 1.25 (1.09–1.43), 2.02 (1.76–2.32), and 2.09 (1.88–2.32) for never smokers, past smokers, exclusive HTP users, dual users, and exclusive cigarette smokers, respectively. In conclusion, exclusive HTP users had lower HDL-C concentrations than never smokers, although higher than exclusive cigarette smokers. Moreover, dual users had HDL-C concentrations similar to those in exclusive cigarette smokers.